Kesadaran Sosiologis Pengelolaan Sampah Pra-TPA dalam Pengendalian Jejak Karbon di Gorontalo: Kajian Literatur - Safira Putri H. Malik; Wawan K. Tolinggi; Irwan Bempah (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
Landfills represent a significant source of greenhouse gas emissions arising from the anaerobic decomposition of organic material that is not managed at source. This literature review departs from the sociological premise that waste management is fundamentally a social problem before it becomes a technical one that ecological values, community norms, social capital, and local wisdom determine waste management effectiveness far more profoundly than infrastructure availability alone. Using environmental sociology as the primary analytical framework, this review examines reputable references from the Scopus database, international institutional reports (World Bank, IPCC), and local empirical studies in Gorontalo. Discussion is organized around three major sociological themes: (1) biospheric values, social identity, and determinants of community pro-environmental behavior; (2) social norms, social capital, and the role of Huyula local wisdom in collective environmental management in Gorontalo; and (3) sociological implications for the design of pre-landfill waste management programs. Synthesis findings indicate that the absence of ecological value internalization and the discontinuation of community socialization constitute the sociological root causes of increasing landfill burdens. Conversely, communities with internalized biospheric values, rooted sorting norms, and structured social capital such as the Huyula tradition in Gorontalo possess substantially greater capacity to realize effective and sustainable pre-landfill waste management.